Antenatal and Delivery Outcomes in Twin Pregnant Women after Uterine Adenomyomectomy: Summary of 5 Cases - Kweon, Sojeong; Lee, Jeong Soo; Kim, Sujin; Kwack, Jae Young; Kwon, Yong-Soon (Perinatology (Online), 2023)
This study was conducted to assess the antenatal and delivery outcomes of women pregnant with twins who previously received conservative surgical treatment for severe diffuse uterine adenomyosis. The study was a retrospective analysis of the medical records of women pregnant with twins with a history of adenomyomectomy between 2019 and 2022. Five patients who conceived multiple pregnancies were included. One patient conceived naturally, and 4 patients received reproduction assistance via in vitro fertilization (IVF). One patient had a triplet pregnancy. However, 1 fetus underwent a selective abortion, and 1 of the remaining 2 fetuses died. All patients underwent cesarean section deliveries. One patient failed to deliver twins because of a uterine rupture at 30 weeks, and the twins expired. Except for 1 demised baby, a total of 7 babies were born by transverse lower segment cesarean delivery. Four cesarean preterm deliveries were performed due to the onset of labor at 34, 33, 30, and 28 weeks of gestational age. Baby weights ranged from 1,910 to 2,050 g. All 7 babies were admitted to the newborn intensive care unit for preterm care. One baby expired, and 6 babies were discharged healthy without any major complications. Twin pregnancy after adenomyomectomy might represent a high antenatal care risk for both the fetuses and the mothers. Early admission for continuous monitoring and emergency cesarean delivery should be performed to prevent uterine rupture. In addition, single embryo transfer is recommended for patients who undergo IVF after adenomyomectomy for better maternal and fetal outcomes. KCI Citation Count: 0